The Use of Proton Pump Inhibitors in Managing Preeclampsia: A Systematic Review - Avensia, Taura; Bahardiani, Dinda Tsania (Medicinus, 2025)
Background: Maternal mortality remains a major global challenge, with preeclampsia (PE) as a leading cause after hemorrhage and infection. PE, a hypertensive disorder after 20 weeks of gestation, affects over. 4 million pregnancies annually, causing 50,000–70,000 maternal deaths. If untreated, it can lead to severe complications like eclampsia, HELLP syndrome, organ failure, and death. It also increases risks for the fetus, including low birth weight, preterm birth, and perinatal mortality. Early and effective management is crucial. Research suggests proton pump inhibitors (PPIs) may help by reducing sFlt-1 secretion, offering potential treatment options. Methods: A literature search was conducted in PubMed, ScienceDirect, Directory of Open Access Journals, and Cochrane Library, yielding 354 studies. Two studies meeting inclusion and exclusion criteria were included in this review. Result: Omeprazole and esomeprazole reduced sFlt-1 levels and increased PlGF levels in PE pregnancies, although the changes were not statistically significant. Esomeprazole increased sFlt-1 levels specifically in placental tissue. No adverse effects were reported with PPI use in the included studies. Conclusions: PPIs (omeprazole or esomeprazole 40 mg) show potential as safe therapies for managing preeclampsia, with minimal side effects, by reducing sFlt-1 levels and increasing PlGF levels. Further research is needed to confirm these findings.